The influence of a top-heavy integrated galactic IMF and dust on the chemical evolution of high-redshift starbursts. Issue 2 (7th April 2020) - Palla, M; Calura, F; Matteucci, F; Fan, X L; Vincenzo, F; Lacchin, E
ABSTRACT: We study the effects of the integrated galactic initial mass function (IGIMF) and dust evolution on the abundance patterns of high redshift starburst galaxies. In our chemical models, the rapid collapse of gas clouds triggers an intense and rapid star formation episode, which lasts until the onset of a galactic wind, powered by the thermal energy injected by stellar winds and supernova explosions. Our models follow the evolution of several chemical elements (C, N, α-elements, and Fe) both in the gas and dust phases. We test different values of β, the slope of the embedded cluster mass function for the IGIMF, where lower β values imply a more top-heavy initial mass function (IMF). The computed abundances are compared to high-quality abundance measurements obtained in lensed galaxies and from composite spectra in large samples of star-forming galaxies in the redshift range 2 ≲ z ≲ 3. The adoption of the IGIMF causes a sensible increase of the rate of star formation with respect to a standard Salpeter IMF, with a strong impact on chemical evolution. We find that in order to reproduce the observed abundance patterns in these galaxies, either we need a very top-heavy IGIMF (β < 2) or large amounts of dust. In particular, if dust is important, the IGIMF should have β ≥ 2, which means an IMF slightly more top-heavy than the Salpeter one. The evolution of the dust mass with time for galaxies of different mass and IMF is also computed, highlighting that the dust amount increases with a top-heavier IGIMF.